Immunoinformatics guided design of a next generation epitope-based vaccine against Kaposi Sarcoma - Hammadul Hoque; Sumaiya; Mahmudul Hasan; Md Mashiur Rahaman; G.M. Nurnabi Azad Jewel; Shamsul H. Prodhan (Informatics in Medicine Unlocked, 2022)
Kaposi sarcoma-associated herpesvirus (KSHV) is the etiologic agent of Kaposi Sarcoma (KS) and other two B-cell originated malignancies. Despite its familiarity as a direct carcinogen, still there is no permanent treatment or approved vaccine. This work intended to develop a multi-epitope vaccine aiming KSHV's key glycoproteins involved in viral entry. After applying rigorous immunoinformatics algorithms and numerous immunological filters, a unique vaccine containing multiple CTL, HTL, and BCL epitopes was created. Further, the putative vaccine's overall stability was demonstrated by three molecular dynamics simulations, along with a series of computational evaluations. Docking experiments revealed that the vaccination can make stable interactions with Toll-Like Receptor. Codon optimization and insertion into the cloning vector revealed that the newly designed vaccine candidate could be proficiently expressed in the E. coli system. Finally, an immune simulation was carried out to calibrate the vaccine's potency to trigger an immune response of the host.